TRANSFORMATIONS AND EVOLVING PARADIGM OF LABOUR COMMITMENT IN AN ERA OF EU NEW-GENERATION FREE TRADE AGREEMENTS: FROM LABOUR STANDARDS TO DECENT WORK - Dung Nguyen, Tien (Pécsi Munkajogi Közlemények, 2025)